Clinical characteristics, one-year change in ejection fraction and long-term outcomes in patients with heart failure with mid-range ejection fraction: a multicentre prospective observational study in Catalonia (Spain). Issue 12 (21st December 2017) - Farré, Nuria; Lupon, Josep; Roig, Eulàlia; Gonzalez-Costello, Jose; Vila, Joan; Perez, Silvia; de Antonio, Marta; Solé-González, Eduard; Sánchez-Enrique, Cristina; Moliner, Pedro; Ruiz, Sonia; Enjuanes, C; et al.
Abstract : Objectives: The aim of this study was to analyse baseline characteristics and outcome of patients with heart failure and mid-range left ventricular ejection fraction (HFmrEF, left ventricular ejection fraction (LVEF) 40%–49%) and the effect of 1-year change in LVEF in this group. Setting: Multicentre prospective observational study of ambulatory patients with HF followed up at four university hospitals with dedicated HF units. Participants: Fourteen per cent (n=504) of the 3580 patients included had HFmrEF. Interventions: Baseline characteristics, 1-year LVEF and outcomes were collected. All-cause death, HF hospitalisation and the composite end-point were the primary outcomes. Results: Median follow-up was 3.66 (1.69–6.04) years. All-cause death, HF hospitalisation and the composite end-point were 47%, 35% and 59%, respectively. Outcomes were worse in HF with preserved ejection fraction (HFpEF) (LVEF>50%), without differences between HF with reduced ejection fraction (HFrEF) (LVEF<40%) and HFmrEF (all-cause mortality 52.6% vs 45.8% and 43.8%, respectively, P=0.001). After multivariable Cox regression analyses, no differences in all-cause death and the composite end-point were seen between the three groups. HF hospitalisation and cardiovascular death were not statistically different between patients with HFmrEF and HFrEF. At 1-year follow-up, 62% of patients with HFmrEF had LVEF measured: 24% had LVEF<40%, 43% maintained LVEF 40%–49% and 33% had LVEF>50%. While change in LVEF as continuous variable was not associated with better outcomes, those patients who evolved from HFmrEF to HFpEF did have a better outcome. Those who remained in the HFmrEF and HFrEF groups had higher all-cause mortality after adjustment for age, sex and baseline LVEF (HR 1.96 (95% CI 1.08 to 3.54, P=0.027) and HR 2.01 (95% CI 1.04 to 3.86, P=0.037), respectively). Conclusions: Patients with HFmrEF have a clinical profile in-between HFpEF and HFrEF, without differences in all-cause mortality and the composite end-point between the three groups. At 1 year, patients with HFmrEF exhibited the greatest variability in LVEF and this change was associated with survival.